AN ANALYSIS OF THE SIXTH SEMESTER STUDENT TRANSLATION SKILL AT MUHAMMADIYAH UNIVERSITY OF TANGERANG - Fathimah Az zahro; - - Nargis; Moh Iqbal Firdaus; Yudhie Indra Gunawan (Universitas Muhammadiyah Tangerang, 2021)
This research aimed at analyzing translation accuray of student translation between the source language (SL) in Bahasa and target language (TL) in English and finding out the translation process used by student at Muhammadiyah University of Tangerang. The object of this research is 6th Grade Student at Muhammadiyah University of Tangerang. The researcher focuses on the accuracy of student translation results in range accurate, less accurate and inaccurate based on Accurate Translation Rate proposed by Nababan (2012). The researcher also analyzes the translation process based on Nida and Taber’s theory (1969). In conclusion, researcher found that the accuracy of translation is rated by a lecturer of English Education Study Program of Teachers Training and Education Faculty of Muhammadiyah Tangerang with the results 83,1% translations are accurate, 15,3% translations are less accurate and 1,6.% translation are inaccurate. While, the researcher found that most of translation process used by students is non sequentially process (71%), and the sequentially process is 29%.